Effects of different exercise frequencies on body composition and physical fitness in overweight and obese young school-aged children - Alves, Ana Ruivo (2013)
Introduction: Obesity is considered to be one of the epidemics of the 21st century and the perspective is to increase in children and adolescents¹. Furthermore, physical activity supplies health benefits by increasing children’s aerobic fitness, bone mass and high-density lipoprotein (HDL) cholesterol, and by helping to reduce chronic diseases like obesity and hypertension. Public health physical activity guidelines address the exercise needs of children and adolescents². However, there are few published studies that demonstrate what are the most effective exercise frequencies to obtain better results in body composition and physical fitness. The purpose of this study was to evaluate short-term effects of multicomponent exercise training with different exercise frequencies on body composition (BC) and physical fitness (PF) in overweight and obese young school-aged children.